General Strategy toward Hydrophilic Single Atom Catalysts for Efficient Selective Hydrogenation. Issue 25 (7th July 2022) - Ling, Yuxuan; Ge, Handong; Chen, Jiawen; Zhang, Yuqi; Duan, Yunxia; Liang, Minghui; Guo, Yanjun; Wu, Tai‐Sing; Soo, Yun‐Liang; Yin, Xiong; Ding, Liming; Wang, Leyu
Abstract: Well dispersible and stable single atom catalysts (SACs) with hydrophilic features are highly desirable for selective hydrogenation reactions in hydrophilic solvents towards important chemicals and pharmaceutical intermediates. A general strategy is reported for the fabrication of hydrophilic SACs by cation‐exchange approach. The cation‐exchange between metal ions (M = Ni, Fe, Co, Cu) and Na + ions introduced in the skeleton of metal oxide (TiO2 or ZrO2 ) nanoshells plays the key role in forming M1 /TiO2 and M1 /ZrO2 SACs, which efficiently prevents the aggregation of the exchanged metal ions. The as‐obtained SACs are highly dispersible and stable in hydrophilic solvents including alcohol and water, which greatly facilitates the catalysis reaction in alcohol. The Ni1 /TiO2 SACs have been successfully utilized as catalysts for the selective C=C hydrogenation of cinnamaldehyde to produce phenylpropanal with 98% conversion, over 90% selectivity, good recyclability, and a turnover frequency (TOF) of 102 h −1, overwhelming most reported catalysts including noble metal catalysts. Abstract : A universal "cation‐exchange" strategy has been presented for the preparation of single‐atom catalysts (SACs) on various metal oxides with hydrophilic features. The Ni1 /TiO2 SACs have demonstrated excellent catalytic performance for the selective hydrogenation of C=C in cinnamaldehyde to produce phenylpropanal in isopropanol, with high conversion and selectivity, good recyclability, and a turnover frequency (TOF) of up to 102 h −1 .